Vibration Failure Analysis and Countermeasures of the Inlet Pipelines at a Gas Compressor Station - Shuangshuang Li; Liwen Zhang; Chunyan Kong (Shock and Vibration)
A gas compressor station only had its about 35% design processing capacity as a result of the abnormal piping vibrations on the inlet pipelines. Characterization, diagnostics, analysis, and elimination of piping vibration were performed. The root causes and sources of the abnormal vibration were investigated by on-site measurements and analysis of vibration and pulsation under various load conditions of compressors. The results revealed that it was not mechanical resonance, but the high pressure pulsation and acoustic resonance occurred on the inlet pipelines, which resulted in the severe vibration. Three different modification models against vibration were proposed by shortening the length of the pipe to avoid acoustic resonance, enlarging the volume of the gathering manifold to buffer pressure pulsation, and adding supports to increase the stiffness. A better modification model was applied by performing modal analysis and fluid-structure interaction (FSI) vibration analysis using the finite element method. The effect of countermeasures was evaluated by vibration and pulsation measurements during operation after modifications, which results showed the level of piping vibration and pressure pulsation was within the allowable limits. The processing capacity of the gas station has reached its design requirement as a result of the desired reduction in vibrations.